Bringing the World Home : Appropriating the West in Late Qing and Early Republican China - Huters, Theodore (Book collections on Project MUSE., 2005)
Bringing the World Home sheds new light on China's vibrant cultural life between 1895 and 1919--a crucial period that marks a watershed between the conservative old regime and the ostensibly iconoclastic New Culture of the 1920s. Although generally overlooked in the effort to understand modern Chinese history, the era has much to teach us about cultural accommodation and is characterized by its own unique intellectual life. This original and probing work traces the most significant strands of the new post-1895 discourse, concentrating on the anxieties inherent in a complicated process of cultural transformation. It focuses principally on how the need to accommodate the West was reflected in such landmark novels of the period as Wu Jianren's "Strange Events Eyewitnessed in the Past Twenty Years" and Zhu Shouju's "Tides of the Huangpu", which began serial publication in Shanghai in 1916